100% renewable energy transition: Pathways and implementation - Claudia Kemfert; Christian Breyer; Pao-Yu Oei (MDPI, 2019)
The aim of this Special Issue is to collect research papers that address the above issues using novel methods from any adequate perspective, including economic analysis, modeling of systems, behavioral forecasting, and policy assessment. The issue will include, but is not be limited to: • Local control schemes and algorithms for distributed generation systems • Centralized and decentralized sustainable energy management strategies • Communication architectures, protocols and properties of practical applications • Topologies of distributed generation systems improving flexibility, efficiency and power quality • Practical issues in the control design and implementation of distributed generation systems • Energy transition studies for optimized pathway options aiming for high levels of sustainability
Keywords: 330